EVALUASI USABILITY WEBSITE ABCD UNJA MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Anggoro, Dika (JUSS (Jurnal Sains dan Sistem Informasi), 2021)
Based on the results of data calculations and discussions on the research that has been done, the SUS score of 80.9 was obtained from a sample of Jambi University students. On the Grade Scale, the two SUS scores can be seen to be in Grade A, which indicates the score is very good because it is above average. In the Adjective Ratings, it can be grouped that the use of the UNJA ABCD website according to the respondents is classified as excellent (excellent). In Acceptability, the use of the UNJA ABCD website which has been applied to the University of Jambi can be accepted and used in general by respondents. The Net Promoter Score (NPS) is in the promoter classification where the respondents in this study will most likely promote or notify the UNJA ABCD website to friends or people around them to be able to use this website. Therefore, it can be concluded from this research that ABCD UNJA is easy to use and can also be accepted by users related to the functionality and features of this website itself.